2019
DOI: 10.1186/s12879-019-4686-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of active trachoma among children in Ethiopia: a systematic review and meta-analysis

Abstract: BackgroundTrachoma is the commonest infectious cause of blindness. It is prevalent in areas where personal and community hygiene is poor, and it mainly affects deprived and marginalized communities most importantly in Ethiopia. Hence, the aim of this study was to determine the prevalence and associated factors of active trachoma among children in Ethiopia.MethodA systematic review and meta-analysis was employed to determine the prevalence of active trachoma and associated factors among children in Ethiopia. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 65 publications
(52 reference statements)
5
34
0
Order By: Relevance
“…This finding was similar with studies done in Zala district, Southern Ethiopia [22], Wereilu district, Ethiopia [27] and Uganda [8]. Moreover, this finding was consistent with the systematic review and meta-analysis done in Ethiopia [28]. This is due to the fact that children with unclean faces could be more likely to spread ocular secretions infected with C. trachomatis.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was similar with studies done in Zala district, Southern Ethiopia [22], Wereilu district, Ethiopia [27] and Uganda [8]. Moreover, this finding was consistent with the systematic review and meta-analysis done in Ethiopia [28]. This is due to the fact that children with unclean faces could be more likely to spread ocular secretions infected with C. trachomatis.…”
Section: Discussionsupporting
confidence: 92%
“…Stata, version 15.1 (StataCorp. ), was utilized to collect data and to perform relevant analyses in this meta-analysis (Gebrie et al, 2019;Adane et al, 2020). Each numerical value of the result was presented with a 95% confidence interval (95% CI).…”
Section: Data Synthesis and Statisticsmentioning
confidence: 99%
“…Furthermore, the finding showed that children from households without latrine access developed higher odds of active trachoma in the Amhara region. Plausible explanations might be related to the high endemicity of the diseases in the region [ 37 ] and associated with many studies conducted in the area to alleviate the problems [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethiopia is one of the hardest-hit countries where trachoma is endemic [ 3 ]. According to recent research in Ethiopia, the average prevalence of active trachoma among children was 26.9% [ 39 ]. This prevalence was significantly higher than WHO target for eliminating trachoma [ 2 ].…”
Section: Discussionmentioning
confidence: 99%